Operation pangolin : saving the world's only scaled mammal - Eszterhas, Suzi (2023)
"Pangolins are one of the most poached animals in the world. Yet scientists know very little about them. Discover how pangolin rescuers and researchers such as Thai Nguyen are working to protect these mysterious creatures"--
Introduction: Meet Thai -- What is a pangolin? -- Adaptations for anteating -- Pangolins around the world -- Pangolins in trouble -- Thai to the rescue -- Pangolin checkup -- Happy, healthy pangolins -- A tiny surprise -- Back to the wild -- Teaching people about pangolins -- Zoos on team pangolin -- Solving Pangolin mysteries -- Pangolins need your help
Includes bibliographical references and index
Ages 8-12
Grades 4-6
Keywords: Pangolins -- Juvenile literature; Pangolins -- Behavior -- Juvenile literature; Pangolins -- Habitat -- Juvenile literature; Wildlife conservation -- Juvenile literature; Endangered species -- Juvenile literature; Mammals -- Juvenile literature; Instructional and educational works; Illustrated works